Isolation of antagonistic fungi from local rice and rhizosphere as potential biocontrol agents against Pyricularia oryzae - DIAN EKAWATI SARI; SYLVIA SJAM; ADE ROSMANA; MELINA MELINA; SULFIANI SULFIANI (Society for Indonesian Biodiversity, 2026)
Abstract. Sari DE, Sjam S, Rosmana A, Melina, Sulfiani. 2026. Isolation of antagonistic fungi from local rice and rhizosphere as potential biocontrol agents against Pyricularia oryzae. Biodiversitas 27 (4): d270419. https://doi.org/10.13057/biodiv/d270419. Antagonistic fungi act as biocontrol agents for plant diseases. Pyricularia oryzae, the causative agent of blast disease, is one of the main pathogens affecting rice crops. In Indonesia, this pathogen is a major constraint in rice cultivation. The use of biocontrol agents can be an alternative to control P. oryzae. The purpose of this study was to test fungi isolated from local rice plants and their rhizosphere as control agents for P. oryzae. Samples were randomly collected from two local rice plants and their rhizospheres at different locations. Fungi from the rhizosphere were isolated using serial dilution techniques. At the same time, plant parts, namely roots, stems, and leaves, were sterilized using surface sterilization methods and grown on potato dextrose agar media. Pathogenicity tests used rice seeds as indicator plants. Antagonism tests used the dual-culture method with P. oryzae as the pathogen. The fungal isolates were identified to the genus level. The results revealed that 31 fungal isolates were obtained from local rice plants and their rhizosphere. Pathogenicity tests showed that 29 isolates were non-pathogenic, with seed germination rates on PDA medium averaging 73%-100% and on sterile soil medium averaging 60%-100%. Dual culture tests showed that 11 isolates inhibited the growth of P. oryzae by more than 50%. The most effective isolate was RH4C3, which exhibited up to 82.52% inhibition and showed a significant difference compared to the other fungi, except for isolates RH4C22 and HB3C1. Microscopic identification revealed several genera with the greatest potential as antagonists, namely Trichoderma sp., Paecilomyces sp., Penicillium sp., Nigrospora sp., and Pythium sp. These findings provide insights into the diversity and potential of local biological control agents that utilize antagonistic fungi, their further identification and field application should be undertaken.